Butanol synthesis from ethanol over CuMgAl mixed oxides modified with palladium (II) and indium (III) - Perrone, Olavo Micali [UNESP]; Lobefaro, Francesco; Aresta, Michele; Nocito, Francesco; Boscolo, Mauricio [UNESP]; Dibenedetto, Angela (Elsevier, 2018)
Ethanol conversion to butanol was investigated over mixed oxides derived from hydrotalcites modified with copper, palladium or indium. The reaction was carried out in the 403–573 K temperature range using stainless steel reactors. The presence of indium or palladium in the catalyst influences the temperature of reaction so that it was possible obtain butanol at temperature as low as 423 K. This is in line with the fact that the addition of metals with high hydrogen-transfer capacity makes faster all steps of the reaction with great energy saving. The best selectivity to butanol (65%) was achieved using In-CuMgAl catalysts with 3% of ethanol conversion at a temperature as low as 443 K.
Keywords: Butanol; Copper-hydrotalcite; Ethanol conversion; Heterogeneous catalysis; Indium-hydrotalcite; Palladium-hydrotalcite